Corporate pyramids, geographical distance, and investment efficiency of Chinese state-owned enterprises - Opie, Wei; Tian, Gary Gang; Zhang, Hong Feng (Journal of Banking & Finance, 2019)
We investigate how the state's intervention in the investment decisions of Chinese local SOEs is affected by corporate control distance in the form of pyramidal layers and the geographical distance between the SOEs and their government controllers. Although both the corporate control distance and the geographical distance affect the state's costs of acquiring information about the SOEs, the former is created intentionally by the state to delegate decision rights, and the latter is largely exogenous. We find that local SOEs’ investment efficiency is positively associated with the extensiveness of pyramids but negatively related to the geographical distance. The positive impact of pyramid-building on investment efficiency remains strong even when information costs captured by the geographical distance are low. However, the two distance measures lose their impact on investment efficiency when local governments reclaim control through a vertical interlock of chairman. Our results indicate that the credibility of the government's intention to delegate decision rights is vital to the SOEs’ efficiency when government intervention is the norm in China.